Using of Bejan's Heatline Technique for Analysis of Natural Convection in a Divided Cavity with Differentially Changing Conductive Partition - Koca, Ahmet; Öztop, Hakan Fehmi; Varol, Yasin; Mobedi, Moghtada (Taylor & Francis Inc, 2013)
The issue of laminar natural convection and conduction in enclosures divided by a partition with different thicknesses is investigated numerically. The partition is accepted as conductive at different thermal conductivity ratio. The cavity is filled with air, and it is heated differentially from vertical walls while horizontal walls are adiabatic. The problem is solved for different values of Rayleigh number (10(3)Ra10(6)), thickness ratio of the partition, and thermal conductivity ratio (0.1k10.0). It is found that both heat transfer and flow strength strongly depend on the thermal conductivity ratio of the solid material of partition and Rayleigh numbers.
Keywords: Vertical Walls; Visualization; Enclosures; Transport; Flow